Beyond Surface Learning: Examining Instructional Module Alignment with Deep Learning Principles in Elementary Schools - Neng Nidha, Eneng Nidha Widiarahmi; Mulyasari, Effy (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the alignment of elementary school teaching modules with deep learning principles that emphasize meaningful learning, cognitive involvement, and knowledge transfer capabilities. The research background is based on the tendency of learning in elementary schools that is still oriented towards memorization so that it has not fully encouraged high-level thinking. The research uses a qualitative approach with content analysis design for class V teaching modules in the subjects of Science Studies, Mathematics, and Indonesian Language. The analysis was carried out using the rubric of deep learning indicators which included cognitive depth, conceptual understanding, knowledge transfer, cognitive involvement, and coherence of learning components. The results showed that most of the modules were in the medium alignment category, with indicators of conceptual understanding and cognitive engagement relatively better than indicators of cognitive depth and knowledge transfer. These findings show that module design is still in the transition stage from surface learning to deep learning. Therefore, the development of modules that are more contextual, collaborative, and aligned between objectives, activities, and assessments is needed to improve the quality of meaningful learning in primary schools.